Moving Toward Greater Diversity: A Review of Interventions to Increase Diversity in Nursing Education. (October 2013) - Loftin, Collette; Newman, Susan D.; Gilden, Gail; Bond, Mary Lou; Dumas, Bonnie P.
Purpose: To report the results of a comprehensive review of interventions used by nursing programs to increase the success of underrepresented minority nursing students graduating from prelicensure programs.Design/Method: This review used the five stages of review methodology described but Whittemore and Knafl to extract data, summarize, and synthesize findings of 11 studies included in this review. Intervention strategies were organized using concepts of Jeffreys's Nursing Undergraduate Retention and Success model.Findings: Interventions were designed to improve recruitment, retention, and academic performance through a variety of innovative activities.Conclusions: This review highlighted the necessity for future researchers to report in-depth and detailed information about the implementation of interventions. Comprehensive information about the program, faculty, setting, interventions, and challenges faced during implementation were often missing from these reports, making replication difficult.